Finite-time attitude tracking control for spacecraft based on backstepping method with input saturation - Yanmin Ren; Aijia Xing (PLoS ONE, 2025)
In this paper, the finite-time attitude tracking control problem for spacecraft based on the backstepping method is addressed. Firstly, a finite-time controller is designed, which can provide robustness for external disturbance by employing an improved adaptation law. Secondly, a novel finite-time controller with input saturation is proposed by introducing the hyperbolic function and auxiliary system to guarantee the control torques below a predetermined value. The above two controllers are continuous, thus, they are chattering-free. Finally, simulation results are presented to illustrate the effectiveness of the control strategies.